2007
DOI: 10.1097/01.ccm.0000251130.69568.87
|View full text |Cite
|
Sign up to set email alerts
|

Early activity is feasible and safe in respiratory failure patients*

Abstract: We conclude that early activity is feasible and safe in respiratory failure patients. A majority of survivors (69%) were able to ambulate >100 feet at RICU discharge. Early activity is a candidate therapy to prevent or treat the neuromuscular complications of critical illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
624
2
64

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 771 publications
(720 citation statements)
references
References 21 publications
13
624
2
64
Order By: Relevance
“…3,11,12 In particular, patients may receive a prompt and dedicated physiotherapy rehabilitation program in chronic ventilator facilities, 1,3,13 and transfer from an ICU to a chronic ventilator facility substantially improved patients' ambulation and activities of daily life irrespective of the underlying pathophysiology, avoiding unnecessary immobilization 14 . To date, the role of comprehensive rehabilitation in critically ill adults still remains controversial 13 or not fully established 15 : patients who have survived a recent acute respiratory failure (ARF) event can benefit from an individually tailored physiotherapy rehabilitation program that improves clinical indices, respiratory and peripheral muscle strength, activities of daily life, exercise tolerance, and disability scores. 14,[16][17][18][19][20][21][22][23][24] Once the precipitating cause of the ARF episode has been solved, these chronically ill patients still require care due to their huge motor disabilities, clinical dependence (oxygen, mechanical ventilation, nutritional, and communication device needs), and nursing necessities, 3 which the care team (physiotherapist, doctor, and nurse) must measure to better guide the daily care of the patient. No study has been performed with a large patient sample to investigate patient needs with these 3 different perspectives combined.…”
Section: Introductionmentioning
confidence: 99%
“…3,11,12 In particular, patients may receive a prompt and dedicated physiotherapy rehabilitation program in chronic ventilator facilities, 1,3,13 and transfer from an ICU to a chronic ventilator facility substantially improved patients' ambulation and activities of daily life irrespective of the underlying pathophysiology, avoiding unnecessary immobilization 14 . To date, the role of comprehensive rehabilitation in critically ill adults still remains controversial 13 or not fully established 15 : patients who have survived a recent acute respiratory failure (ARF) event can benefit from an individually tailored physiotherapy rehabilitation program that improves clinical indices, respiratory and peripheral muscle strength, activities of daily life, exercise tolerance, and disability scores. 14,[16][17][18][19][20][21][22][23][24] Once the precipitating cause of the ARF episode has been solved, these chronically ill patients still require care due to their huge motor disabilities, clinical dependence (oxygen, mechanical ventilation, nutritional, and communication device needs), and nursing necessities, 3 which the care team (physiotherapist, doctor, and nurse) must measure to better guide the daily care of the patient. No study has been performed with a large patient sample to investigate patient needs with these 3 different perspectives combined.…”
Section: Introductionmentioning
confidence: 99%
“…13 Erken ayağa kaldırmanın hastanede yatış süresini azaltarak erken taburcu olma, ameliyat sonrası komplikasyonların görülmesinde azalma, hastane maliyetinin azalması ve hastanın konforu ve günlük yaşama erken dönme üzerinde anlamlı oranda etki ederek hızlı iyileşmeyi sağ-ladığı bilinmektedir. 13,[20][21][22][23][24][25][26][27][28][29][30] Cerrahi hastalarında mobilizasyonun etkilerinin araştırıldığı bir sistematik incelemede; uzun süren immobilizasyonun özellikle yaşlılar, derin ven trombozu olanlar ve ampütasyonlu hastalarda; fonksiyonlarda düşme ve hastaneden kaynaklı komplikasyonların artmasına neden olduğu bildirilmektedir. 25 Erken ayağa kaldırmanın olumlu etkileri dikkate alındığında; yatan hasta mobilizasyonunun, hastane ortamında klinik hemşireleri için daha yüksek öncelikle uygulanması gerektiği belirtilmektedir.…”
Section: Discussionunclassified
“…Th e investigators demonstrated that 69.4% of patients were able to walk a minimum of 200 feet, with less than 3% being incapable of activity during their ICU admission. Th is impressive level of mobilization was achieved at the expense of very few adverse events; a total of 14 occurred over 1,449 activity events, including falls to the knees without injury, acute desaturation, changes in systolic blood pressure, and removal of feeding tube [11].…”
Section: Early Mobilizationmentioning
confidence: 99%
“…Members included respiratory, physical, and occupational therapists, a nurse and a critical care technician [11][12][13][14]. In addition to the team, it was concluded that a coordinated sedation strategy was important to the success of the early mobilization intervention.…”
Section: Early Mobilizationmentioning
confidence: 99%
See 1 more Smart Citation